PENGARUH KEPUASAN TERHADAP KELENGKAPAN REKAM MEDIS DI RUMAH SAKIT UMUM DAERAH ADJIDARMO - Lily Widjaya, SKM, MM -; Lusiana Apriani; Mentari Nur Indah Sari (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2018)
The purpose of the study to analyze the effect of job satisfaction on completeness of filling medical record. The type of research is observational analytic with cross sectional approach. The population of this study is the outpatient physician and specialist doctor who treated the patients as much as 74 people. A sample size of 30 people were taken with accidental sampling technique. This research instrument is a questionnaire. Data analysis using multiple regression analysis. The results showed the value of F = 12.257> Ftabel = 2.65 or p value <0.05. Individual test is shown at p <0.05 in X2, X3, X5, p value of each variable; 0.021; 0.019; 0.033. The conclusions in this study are the variables that affect the completeness of medical record that is the satisfaction of compensation, satisfaction toward Leadership, satisfaction of promotion.